2017
DOI: 10.1016/j.redox.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol supplementation increases vitamin C levels in vivo. A human volunteer trial

Abstract: Hydroxytyrosol (HT) is a main phenolic component of olive oil. In this study, we investigated the safety and effects produced by HT purified (99.5%) from olive mill waste. HT was administered at a daily dosage of 45 mg for 8 weeks to volunteers with mild hyperlipidemia (n=14). We measured markers of cardiovascular disease risk, enzyme markers of several clinical conditions, hematology, antioxidant parameters, vitamins and minerals at baseline (T0), 4 weeks (T4) and 8 weeks (T8). The values obtained at T4 and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 43 publications
(53 reference statements)
1
46
0
1
Order By: Relevance
“…have emerged in the nutraceutical and functional food markets due to their notable antioxidant activity and capacity to reduce the risk of cardiovascular diseases, as well as their protective effect against oxidative DNA damage . Among them, hydroxytyrosol (HT, 3,4‐dihydroxyphenyl ethanol) possesses the highest in vitro antioxidant activity and displays anti‐inflammatory, neuroprotective and antitumoral properties . In fact, HT is the only polyphenol in the market that supports a European Food Safety Authority health claim .…”
Section: Introductionmentioning
confidence: 99%
“…have emerged in the nutraceutical and functional food markets due to their notable antioxidant activity and capacity to reduce the risk of cardiovascular diseases, as well as their protective effect against oxidative DNA damage . Among them, hydroxytyrosol (HT, 3,4‐dihydroxyphenyl ethanol) possesses the highest in vitro antioxidant activity and displays anti‐inflammatory, neuroprotective and antitumoral properties . In fact, HT is the only polyphenol in the market that supports a European Food Safety Authority health claim .…”
Section: Introductionmentioning
confidence: 99%
“…The only two human studies of HT available thus far have been performed by Lopez‐Huertas and collaborators (Gonzalez‐Santiago, Fonolla, & Lopez‐Huertas, ; Lopez‐Huertas & Fonolla, ). In the former, the authors confirmed human absorption of HT and recorded its transient association with LDL, confirming data by Bonanome et al (), who administered EVOO rather than pure HT.…”
Section: Human Studiesmentioning
confidence: 99%
“…However, other studies suggested that the main HT effects are a consequence of increasing endogenous vitamin C levels, since it did not influence blood lipids, inflammatory markers, liver or kidney functions [89]. In particular, HT has been shown to beneficially impact the hemostatic profile, exerting antiplatelet and antithrombotic properties [25,91].…”
Section: Olive Oil and Phenolic Compoundsmentioning
confidence: 99%